CMET-35. COMPETING RISKS ANALYSIS OF FACTORS INFLUENCING DEVELOPMENT OF LEPTOMENINGEAL METASTASIS IN BREAST CANCER PATIENTS RECEIVING STEREOTACTIC RADIOSURGERY FOR LIMITED BRAIN METASTASES. (11th November 2019) - Zhang, Michael; Lazar, Ann; Chan, Jason; Xu, Chelsea; Anderson, August; Villanueva-Meyer, Javier; McDermott, Mike; Melisko, Michelle; Sneed, Patricia; Morin, Olivier; Braunstein, Steve
Abstract: Leptomeningeal metastasis (LM) is a late stage manifestation of advanced breast cancer frequently managed with whole brain radiotherapy (WBRT) and/or intrathecal chemotherapy. A subset of breast cancer patients who undergo stereotactic radiosurgery (SRS) for limited brain metastases (BM) ultimately develop LM. We hypothesized that this subset of high-risk patients may be identified by patient, disease, and/or treatment parameters. Clinical records from 133 breast cancer patients from a single institution who underwent SRS for BM between February 2010 and March 2018 were retrospectively analyzed. Variables including histopathology, BM features, systemic disease burden, and prior treatments were analyzed. Cumulative incidence rates were estimated with death as a competing risk. Dichotomous variable cutoffs were based on the 75th percentile value. In our cohort, 27 (20.3%) patients ultimately developed LM. With a median follow up of 21.2 months after diagnosis of BM, the actuarial rate of LM at 24 months was 15.2% (95% CI, 8.7%-21.7%). Median OS after diagnosis of LM was 7.0 (95% CI, 3.1–15.4) months. There was significantly increased risk of LM with ≥9 vs < 9 BM at BM diagnosis (28.1% vs 10.8% [24-month actuarial risk], subdistribution HR 2.4, p=0.027), and ≥11 vs < 11 cumulative number of BM treated (25.7% vs 11.7% [24-month actuarial risk], subdistribution HR 2.7, p=0.01). Variables not significantly associated with the risk of LM included tumor receptor status (ER, PR, HER2, triple negative), graded prognostic assessment, KPS, extracranial metastases, total BM volume, prior WBRT, or prior surgical resection. Time intervals between SRS treatments immediately preceding LM diagnosis was not significantly different from other time intervals. In conclusion, patients with a larger number of brain metastases at BM diagnosis (≥9) or cumulatively treated (≥11) appear to be at higher risk of developing LM and may benefit from stronger consideration of WBRT, intrathecal chemotherapy, and/or brain-penetrating systemic therapy.